A proposed algorithm for evaluation and management of pediatric hemophilia patients who present to the emergency department with head trauma. Issue 9 (17th June 2022) - Kracht, M. Jensen; Stein, Amy; Knoll, Christine; Badia Alonso, Priscila; Gomez, Esteban; Quarmyne, Maa‐Ohui; Shah, Sanjay; Gendreau, Joanna
Abstract: Hemophilia is the deficiency of plasma clotting factor VIII (hemophilia A) or IX (hemophilia B) where management focuses on the prevention and treatment of acute bleeding symptoms and their sequelae. The most concerning risk is for life‐threatening bleeding, including intracranial hemorrhage (ICH), which is caused by head trauma. Guidelines exist for the evaluation and management of pediatric head trauma, including the Pediatric Emergency Care Applied Research Network (PECARN) protocol, but limited evidence exists for when hemophilia patients present to the emergency department (ED), specifically with head trauma. Literature is limited regarding ICH and hemophilia, which further supports the culture of uncertainty among providers. The objective of this study is to conduct a retrospective chart review to determine the prevalence and clinical characteristics of ICH, and to describe computed tomography (CT) scan use in hemophilia patients who present to Phoenix Children's Hospital (PCH) ED with head trauma from January 1, 2007 to June 1, 2019. A total of 89 ED visits and 43 patients met inclusion criteria, and prevalence of ICH was determined to be 4% with the patients presenting with varied clinical characteristics and few commonalities. Using these data, we propose a new algorithm to aid clinicians in determining the need for CT scan in pediatric hemophilia patients who present to the ED with head trauma.